IPTEKS AKUNTANSI BERBASIS AKRUAL PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SULAWESI UTARA - Dalipang, Marre Ika; Apita, Grisela Vivi; Naibaho, Karlina; Manossoh, Hendrik (Universitas Sam Ratulangi, 2018)
Dinas Tenaga Kerja Dan Transmigrasi Province of Sulawesi Utara (North Sulawesi Disnakertrans) is a government organization established based on the Presidential Regulation Number. 18 of 2015 which discusses the Ministry of Manpower, Ministry of Manpower and Transmigration has the task of regulating government affairs in the field of labor and to assist the President's work in regulating government. The Ministry of Manpower and Transmigration as a government organization that uses accrual-based Government Information Systems as regulated in Peraturan Pemerintah No. 71 of 2010 contains accounting standards used by the government that regulate the financial statements of an institution. Financial statements are a description of the performance of an agency. This study aims to raise about the problems that exist in the application of accrual-based government accounting systems.Keywords : Accrual based government Information Systems